Prática de análise linguística no trabalho com os gêneros discursivos: em foco, a produção e a reescrita textual - Gedoz, Sueli (2015)
The research that I present in this study refers to the practice of linguistic analysis associated with the work with the production and textual rewritten. This is a research grounded on the assumptions of Applied Linguistics, in the interpretative qualitative approach, using the ethnographic perspective and the action research as methodological design. The unrest which led to the work rests on the question of how the practice of linguistic analysis, understood as routing that goes beyond the work with the grammar rules, can contribute to the process of production and rewriting texts in the classroom. In order to answer this question, the goal is to investigate the contributions of work and linguistic analysis to the process of production and rewriting texts, focusing on a group of 7th grade of elementary school. Investigative cut takes the text, organized a speech genre as a starting point and guiding element of the teaching of Portuguese Language. The theoretical framework that I use bolsters on the Dialogic Discourse Analysis and the sociological method of approach to genres as Bakhtin/Voloshinov (2004 [1929]) and Bakhtin (2011 [1979]). Also, turn to sources that give the linguistic analysis of practices, production and textual rewriting a dialogical bias at work with language. Guided me in this theoretical orientation and in the context of the classroom, I realized results that indicate the need for partnership between all discursive practices that organize the teaching of Portuguese. With respect to focused practices (linguistic analysis, writing, rewriting), I consider that all are pervaded and subsidized by linguistic analysis, for producing and rewrite texts requires arguably the analysis of linguistic and discursive elements that make up the written production.